Evaluation of demulsifiers efficiency for coal tar dehydration according to the value of its viscosity reduction - L. P. Bannikov; D. V. Miroshnichenko; O. L. Borisenko; A. L. Bannikov (Хімія, фізика та технологія поверхні)
For the first time, the relationship between the efficiency of dehydration and the value of reducing the viscosity of the coal tar by adding demulsifier has been studied for “water in tar” emulsions. The dewatering of coal tar emulsions was investigated using 12 demulsifiers with different relative water solubility indices (RSN = 8.2–14.5) for tars of different pyrolysis grades. The effect of a series of demulsifiers on the viscosity of the dispersion medium of “water-in-tar” emulsions was studied. A low-pyrolysis tar was taken as a model of dispersion medium of emulsions with 1.2 % moisture content and 1.0 % of quinoline insoluble substances. A bottle test was used for a comparative evaluation of the demulsifying activity. The rheological characteristics of the studied tars were determined with a rotational controlled-shear rate rheometer Brookfield DV2T in a temperature range between 30 and 65 °C. When demulsifiers were added to the tar and the mixture was aged for 24 h, a decrease in viscosity was observed. When measured without withstanding, the viscosity of the mixture decreases in some cases only at a sufficiently high heating temperature (58 °C). The comparison of the dewatering efficiency with the mixture viscosity at 58 °C shows a linear dependence: the more the tar viscosity decreases when the demulsifier is added, the higher the dewatering efficiency when using this demulsifier for tars of different pyrolytic degree. Decreasing the viscosity of the tar promotes the coalescence of water drops and the diffusion rate of the demulsifier through the dispersion medium to the water-tar interface, which increases the efficiency of dewatering. The selectivity of tar dehydration by the studied demulsifiers is preserved for both low- and high-pyrolyzed coal tars. In the area of low viscosity reduction of the dispersion medium, the role of RSN is considerably higher, and an increase in the hydrophilicity of the reagent contributes to better dehydration. This may be due to the increased wetting ability of demulsifiers concerning emulsion stabilizers.